2019
DOI: 10.1159/000504652
|View full text |Cite
|
Sign up to set email alerts
|

How to Integrate Personalized Medicine into Prevention? Recommendations from the Personalized Prevention of Chronic Diseases (PRECeDI) Consortium

Abstract: Medical practitioners are increasingly adopting a personalized medicine (PM) approach involving individually tailored patient care. The Personalized Prevention of Chronic Diseases (PRECeDI) consortium project, funded within the Marie Skłodowska Curie Action (MSCA) Research and Innovation Staff Exchange (RISE) scheme, had fostered collaboration on PM research and training with special emphasis on the prevention of chronic diseases. From 2014 to 2018, the PRECeDI consortium trained 50 staff members on personaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Communication and training needs have been also identified as key challenges in the implementation of PM by the European PerMed Consortium [35], while the PRECeDI consortiuum added among its recommendations the training of. of clinical and public health professionals should be promoted with the aim of reducing inappropriate use in healthcare [36].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Communication and training needs have been also identified as key challenges in the implementation of PM by the European PerMed Consortium [35], while the PRECeDI consortiuum added among its recommendations the training of. of clinical and public health professionals should be promoted with the aim of reducing inappropriate use in healthcare [36].…”
Section: Plos Onementioning
confidence: 99%
“…It seems clear from these findings, therefore, that greater knowledge of genomics and personalized medicine among health professionals not directly involved in genetics would improve the capacity of health systems to incorporate new genomic technologies [11][12][13][14]35]. Increasing PH capability in genomics could also help to avoid uncontrolled implementation of technologies without proven benefits, which can lead to inappropriate management of patients, detrimental effects on patient health, and waste of financial resources [36]. Our results are in line with the findings of two surveys on the genomics knowledge and attitudes of PH educators conducted respectively in Italy and the US [22,45], showing that knowledge is a significant predictor of positive attitudes towards the use of genetic testing and the delivery of genetic services in PH.…”
Section: Plos Onementioning
confidence: 99%
“…Nowadays, there is a tendency towards moving away from the “ one test, one drug ” model that has defined companion diagnostics to utilize biomarker panels. There is also an expectation that this may lead to better targeting of preventive interventions by defining the disease and targeting the treatment based on a person’s molecular pathology (Boccia et al 2019 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…3 More than 10 years later, however, we are still struggling to collect high quality evidences on the efficacy, effectiveness and efficiency of personalized approaches in prevention, ideally in the context of broad Health Technology Assessment evaluations. 4 Additionally, we need to engage public health professionals. In 2018, some scientists argued that whereas public health starts with populations, the word 'precision' or personalized implies a concern only with individuals.…”
mentioning
confidence: 99%
“…A recent economic evaluation found that fortifying wheat flour with vitamin D in England and Wales would prevent 10 million new cases and save the National Health Services' budget £65 million. 4 Adding flour fortification to the current policy was found to be…”
mentioning
confidence: 99%